Pengaruh Efektivitas Penerimaan Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Aceh Timur - Endra Gunawan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
The implementation of regional autonomy is a manifestation of independence in implementing regional autonomy can be seen from the receipt of Regional Original Revenue, local taxes and retribution is one of the largest sources of income to increase Regional Original Revenue. This study aims to look at the level of effectiveness of regional tax revenues and levies as well as their effect on Regional Original Income in East Aceh District in 2011-2015. This study uses data collection techniques through documentation, namely secondary data in the form of Budget Realization Report of East Aceh District. Based on the results of data management using the SPSS application, it shows that (1) the effectiveness of local tax revenues during 2011-2015 is categorized as very effective. (2) the effectiveness of the receipt of regional levies within the period 2011-2015 is at a fairly effective level. (3) the effectiveness of local taxes has a significant effect on the Regional Original Income with a sig value. 0.001 <0.05. (4) the effectiveness of local taxes has a significant effect on Regional Original Income with a sig value. 0,000 <0,05.